Diagnosing early Barrett’s neoplasia and oesophageal squamous cell neoplasia by bioimpedance spectroscopy in human tissue - Knabe, Mate; Kurz, Christian; Knoll, Thorsten; Velten, Thomas; Vieth, Michael; Manner, Hendrik; Ell, Christian; Pech, Oliver (United European Gastroenterology Journal, 2013)
Background: Detection of early oesophageal cancer in surrounding normal tissue can be challenging, but detection is essential to determine the subsequent treatment. Dysplastic tissue can be detected by using electrical impedance spectroscopy (EIS). Objective: The aim of the present study was to evaluate the feasibility and value of EIS in the diagnosis of oesophageal neoplasia. Methods: This prospective ex-vivo study included 23 patients with early oesophageal cancer (17 with Barrett’s cancer and six with early squamous cell cancer). Immediately after endoscopic resection, the electrical properties of the resected specimens were investigated using a pencil probe (5 mm in diameter, frequency range from 100 Hz to 1MHz). Punch biopsies were taken from the measured site in order to compare the results of EIS with histology. Results: EIS was able to detect dysplastic oesophageal mucosa with a high rate of accuracy (82% in Barrett’s oesophagus and 100% in squamous oesophagus) A total of 54 different sites in 26 tumours were evaluated. Conclusions: EIS was able to differentiate reliably between non-neoplastic and neoplastic oesophageal mucosa. Using EIS, it might be possible to use it for targeted biopsies and to avoid unnecessary biopsies during cancer surveillance in future.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett’s carcinoma; Early oesophageal cancer; Squamous cell cancer; Surveillance; Target biopsy